Global prevalence of congenital heart diseases in infants: a systematic review and meta-analysis - Salari, Nader; Faryadras, Fateme; Shohaimi, Shamarina; Jalili, Faramarz; Hasheminezhad, Razie; Babajani, Fateme; Mohammadi, Masoud (Elsevier, 2024)
Background: Congenital heart anomalies, among the most common congenital abnormalities, are the leading cause of mortality resulting from congenital diseases. This study's objective is to investigate the prevalence of congenital heart diseases in infants through a systematic review and meta-analysis. Methods: This study systematically searched electronic databases, including PubMed, Scopus, Science Direct, and Web of Science, for studies reporting the global prevalence of congenital heart diseases in infants up to March 2023. Results: In the review of 16 studies with a total sample size of 35,281,800 individuals, the heterogeneity test (I2) indicated high heterogeneity (I2 = 99.8%), and a random-effects model was used to analyze the results. Accordingly, the global prevalence of congenital heart anomalies in infancy was reported to be 0.003 (95% CI: 0.002–0.004) or more precisely with exact decimals 0.0027 (95% CI: 0.0022–0.0035), which is 0.27 percent, 2.78 per 1000 and 27.8 per 10,000 births. Additionally, the assessment of publication bias in the studies, considering the large sample size, was performed using the Begg and Mazumdar correlation test, which showed no significant publication bias (p = 0.566). Conclusion: Based on the results of this study, it was reported that the global prevalence of congenital heart diseases in infants is increasing annually. Ventricular and atrial septal defects had the highest prevalence, with a higher occurrence in male infants compared to female infants. It is necessary to implement policies to reduce the prevalence of these diseases and prevent infant mortality caused by them.